Controversy Teaching Approaches: Model, Measure, and Teaching Applications. (December 2022) - Allen, Stuart
Controversies are a potentially powerful teaching tool in the management classroom enabling students to explore different perspectives on an issue and to develop their skills in areas such as critical thinking and communication. Controversy is implicit to learning and to leadership and management roles in workplaces where multiple opposing views inevitably exist. Prior research asserts that constructive controversy resolution skills are important to management students. This multipart study presents a model and measure of controversy teaching approaches and explores evidence of their reliability and validity using confirmatory factor analysis and correlations with relevant outcomes and measures. The three studies, with samples of management and leadership students across several U.S. institutions, provide initial evidence of the validity of the model and measure. Multiple perspectives and avoidance were found to be underlying dimensions of instructors' observed approaches to teaching controversial topics. The controversy teaching approaches model and measure used in this study have potential to support instructional development for management educators, as well as further research on controversy teaching. This study also has practical implications for how instructors approach controversies in the classroom and may aid effective teaching and learning.